Polyiodide chain functionalized covalent organic framework material as well as preparation method and application thereof

By designing cationic covalent organic framework materials and forming polyiodine chain structures, the problems of insufficient selectivity and stability of existing iodine adsorption materials in aqueous phase are solved, and efficient and rapid iodine ion adsorption and regeneration performance are achieved, which is suitable for nuclear wastewater treatment and iodine resource recovery.

CN120795265AActive Publication Date: 2025-10-17NANKAI UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510700442.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-28
Publication Date
2025-10-17
Estimated Expiration
2045-05-28

AI Technical Summary

Technical Problem

Existing iodine adsorption materials lack selectivity and stability in aqueous phases, making it difficult to efficiently remove iodide ions in complex environments, which poses particular challenges in nuclear wastewater treatment and iodine resource recovery.

Method used

Cationic covalent organic framework materials were designed and synthesized, and polyiodine chain structures were formed through hydrogen peroxide treatment. Redox reactions and electrostatic interactions were used to achieve efficient adsorption of iodide ions, and hydroxyl groups were introduced into the materials to enhance the adsorption capacity.

Benefits of technology

It achieves ultra-high capacity and rapid kinetic adsorption of aqueous iodide ions, has excellent selectivity, is suitable for complex ionic environments, and the material is renewable and suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120795265A_ABST
    Figure CN120795265A_ABST
Patent Text Reader

Abstract

The invention discloses a polyiodine chain functionalized covalent organic framework material and a preparation method and application thereof, the material is formed by treating a cationic covalent organic framework (iCOF) through hydrogen peroxide, and the cationic covalent organic framework contains a polyiodine chain structure in a pore channel of the cationic covalent organic framework. The polyiodide chain structure comprises I3 <->, I5 <-> and polyiodide anions with higher polymerization degree; the polyiodine chain functionalized covalent organic framework material prepared by the invention has ultrahigh adsorption capacity on water phase iodide ions, and the adsorption capacity is 198-486mg / g and is far higher than that of most reported iodide ion adsorbents. The material provided by the invention has rapid adsorption kinetics, can reach adsorption equilibrium within 60 minutes, and meets the efficiency requirement in practical application.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the field of material science and environmental engineering, in particular to a polyiodide chain functionalized cationic covalent organic framework (iCOF-Iodine) material and a preparation method thereof and application thereof in water phase iodine ion adsorption. The material realizes the efficient adsorption mechanism of "iodine adsorbing iodine" through a special polyiodide chain structure, and can be applied to the fields of nuclear waste water treatment, environmental remediation and iodine resource recovery. BACKGROUND

[0002] Iodine element, as an essential trace element for human body, has important application value in the fields of medicine, agriculture and electronic industry. However, radioactive iodine isotopes (such as 129 I and 131 I) pose a serious threat to the environment and public health in the process of nuclear accidents and nuclear waste treatment due to their volatility, water solubility, bioaccumulation and long half-life. At the same time, the recovery of iodine resources from industrial wastewater and natural brine also has significant economic value. Therefore, it is of great scientific significance and application value to develop efficient and selective iodine ion adsorption materials. Traditional iodine adsorption materials face many challenges in practical applications. Although activated carbon has a large specific surface area, it lacks selectivity in multi-component systems; silver functionalized zeolites have high affinity for iodine ions, but are high in cost, have great environmental impact and low resource utilization efficiency; metal organic frameworks (MOFs) have poor stability in water environment; porous organic polymers (POPs) have improved stability, but often lack structural precision and tunability, making it difficult to optimize performance. Covalent organic frameworks (COFs) have become promising candidates due to their crystallinity, permanent porosity and structural designability, but traditional COFs usually lack functional sites for ion capture, especially in competitive water environment. Integrating permanent ionic properties into COF structure is a promising but not fully explored strategy.

[0003] At present, although various iodine adsorption materials have been reported, most of them are aimed at gaseous molecular iodine (I2) or iodine in organic solvents. Traditional iodine ion adsorbents mainly work through ion exchange mechanism, and their adsorption capacity is limited by the number of cation exchange sites in the material itself, and they are easily disturbed by coexisting ions, so they have poor selectivity in complex environments. Especially in practical application scenarios such as nuclear waste water treatment, environmental remediation and iodine resource recovery, there are often complex ion environments, which puts higher requirements on the selectivity and stability of the materials. Therefore, it is of great scientific significance and application value to develop a new type of material that can be used for efficient and selective adsorption of iodine ions in water phase. SUMMARY

[0004] The present application aims to at least partially solve one of the technical problems in the related art, and for this purpose, the present application provides a polyiodide chain functionalized covalent organic framework material and a preparation method and application thereof. The present application successfully realizes ultra-high capacity, fast kinetics and excellent selective adsorption of iodine ions in water by designing and synthesizing a cationic covalent organic framework, and treating the framework with hydrogen peroxide to form a polyiodide chain structure inside the framework, thereby providing a new technical path for nuclear waste treatment, environmental remediation and iodine resource recovery.

[0005] The present application adopts the following technical solutions:

[0006] In a first aspect,

[0007] The present application provides a polyiodide chain functionalized covalent organic framework material, which is formed by treating a cationic covalent organic framework (iCOF) with hydrogen peroxide, wherein the cationic covalent organic framework contains a polyiodide chain structure in its pore channel, and the polyiodide chain structure includes polyiodide anions of I3 - , I5 - , and higher polymerization degree (I7 - , etc.).

[0008] The cationic covalent organic framework is synthesized by Schiff base condensation reaction of 1,2,3-triaminoguanidine hydrochloride and aromatic dialdehyde, and the aromatic dialdehyde is at least one selected from naphthalene-2,6-dicarboxaldehyde (Nap), 2,6-dihydroxynaphthalene-1,5-dicarboxaldehyde (Nap-OH), 4,4-biphenyldicarboxaldehyde (BP), and 3,3'-dihydroxy-[1,1'-biphenyl]-4,4'-dicarboxaldehyde (BP-OH).

[0009] More preferably, the aromatic dialdehyde is at least one selected from 2,6-dihydroxynaphthalene-1,5-dicarboxaldehyde (Nap-OH) and 3,3'-dihydroxy-[1,1'-biphenyl]-4,4'-dicarboxaldehyde (BP-OH).

[0010] In a second aspect,

[0011] The present application provides a preparation method of the above-mentioned polyiodide chain functionalized covalent organic framework material, which comprises the following steps:

[0012] S1: 1,2,3-triaminoguanidine hydrochloride and aromatic dialdehyde are mixed according to a molar ratio of 1:(1.5-3), dissolved in a mixed solvent, and ice acetic acid solution is added as a catalyst, and sufficient potassium iodide or sodium iodide (≥0.18 g / mL) is added as a template reagent; the aromatic dialdehyde is at least one selected from naphthalene-2,6-dicarboxaldehyde (Nap), 2,6-dihydroxynaphthalene-1,5-dicarboxaldehyde (Nap-OH), 4,4-biphenyldicarboxaldehyde (BP), and 3,3'-dihydroxy-[1,1'-biphenyl]-4,4'-dicarboxaldehyde (BP-OH).

[0013] S2: reacting the mixed solution of step S1 in a closed reaction kettle at 80-120°C for 24-72 hours;

[0014] S3: collecting the reaction product by filtration, washing, then soaking in saturated ammonium bicarbonate solution at room temperature for 4-8 hours, adding isopropyl alcohol to the saturated ammonium bicarbonate solution, continuing to stir for 0.5-2 hours, filtering to separate the solid product, and then drying at 75-100°C for 10-24 hours to obtain iCOF-I - (cationic covalent organic framework with iodine ions as counter ions);

[0015] S4: dispersing iCOF-I - in an aqueous solution containing 5%-30% hydrogen peroxide, stirring at room temperature for 6-12 hours;

[0016] S5: filtering the treated product, washing with DMF first, then washing with deionized water until neutral, then washing with anhydrous ethanol, and finally drying at 75-100°C for 10-24 hours to obtain the polyiodine chain functionalized covalent organic framework material (iCOF-Iodine).

[0017] In the scheme of the present application, in step S1, a template method is adopted, i.e. a sufficient amount of potassium iodide or sodium iodide (≥0.18 g / mL) crystal is added as a template in the synthesis reaction system to control the framework morphology and simultaneously introduce iodine ions as counter ions.

[0018] More preferably, the aromatic dialdehyde is at least one selected from 2,6-dihydroxynaphthalene-1,5-dialdehyde (Nap-OH) and 3,3'-dihydroxy-[1,1'-biphenyl]-4,4'-dialdehyde (BP-OH). In this way, the cationic covalent organic framework contains hydroxyl functional groups, which enhance the adsorption capacity of the framework for iodine ions through hydrogen bonding.

[0019] More preferably, the aromatic dialdehyde is 2,6-dihydroxynaphthalene-1,5-dialdehyde (Nap-OH), and the maximum adsorption capacity of the polyiodine chain functionalized covalent organic framework material (Nap-OH-COF-Iodine) prepared therefrom for aqueous iodine ions reaches 486 mg / g.

[0020] In some embodiments, the mixed solvent in step S1 is a mixture of 1,4-dioxane and mesitylene, and further preferably, the volume ratio of the two is (1-2):1, or a mixture of o-dichlorobenzene and n-butanol, and further preferably, the volume ratio of the two is (1-2):1.

[0021] In some embodiments, when the aromatic dialdehyde is selected from naphthalene-2,6-dicarboxaldehyde (Nap) or 2,6-dihydroxynaphthalene-1,5-dicarboxaldehyde (Nap-OH), the mixed solvent is a mixture of 1,4-dioxane and mesitylene in a volume ratio of (1-2):1; when the aromatic dialdehyde is selected from 4,4-biphenyldicarboxaldehyde (BP) or 3,3'-dihydroxy-[1,1'-biphenyl]-4,4'-dicarboxaldehyde (BP-OH), the mixed solvent is a mixture of o-dichlorobenzene and n-butanol in a volume ratio of (1-2):1.

[0022] In some embodiments, the concentration of the glacial acetic acid solution is 6-9M, and the volume ratio of the glacial acetic acid solution to the mixed solvent is 1:(3-10).

[0023] In some embodiments, when the aromatic dialdehyde is selected from naphthalene-2,6-dicarboxaldehyde (Nap) or 2,6-dihydroxynaphthalene-1,5-dicarboxaldehyde (Nap-OH), the mixed solvent is a mixture of 1,4-dioxane and mesitylene, the concentration of the glacial acetic acid solution is 6M, and the volume ratio of 1,4-dioxane, mesitylene, and 6M glacial acetic acid solution is 6:3:1.

[0024] In some embodiments, when the aromatic dialdehyde is selected from 4,4-biphenyldicarboxaldehyde (BP) or 3,3'-dihydroxy-[1,1'-biphenyl]-4,4'-dicarboxaldehyde (BP-OH), the mixed solvent is a mixture of o-dichlorobenzene and n-butanol, the concentration of the glacial acetic acid solution is 6M, and the volume ratio of o-dichlorobenzene, n-butanol, and 6M glacial acetic acid solution is 5:5:1.

[0025] In some embodiments, in step S3, the washing refers to sequentially washing the reaction product with N,N-dimethylformamide (DMF), deionized water, tetrahydrofuran (THF), and dichloromethane.

[0026] In some embodiments, the concentration of the hydrogen peroxide solution in step S4 is 10%.

[0027] The third aspect,

[0028] The application also provides the use of the above-mentioned polyiodide chain functionalized covalent organic framework material for adsorbing (removing) iodine ions in a water body.

[0029] In the above-mentioned use, the material captures iodine ions in the water body through the following adsorption mechanisms:

[0030] (a) The polyiodide chains pre-formed in the cationic covalent organic framework serve as adsorption sites, and iodine ions in the water body are oxidized to generate more polyiodide anions through redox reactions;

[0031] (b) The cationic covalent organic framework adsorbs iodine ions through electrostatic interactions;

[0032] (c) when a hydroxyl group is present in the cationic covalent organic framework, the hydroxyl group in the cationic covalent organic framework assists in adsorbing iodine ions through hydrogen bonding;

[0033] (d) specific binding between the polyiodide chain and iodine ions is formed through a charge transfer reaction and a halogen bond.

[0034] In some embodiments of the application, the adsorption process adopts batch adsorption or continuous flow adsorption.

[0035] In some embodiments of the application, the batch adsorption refers to directly adding the polyiodide chain functionalized covalent organic framework material to an aqueous solution containing iodine ions, stirring for adsorption at room temperature, and separating after adsorption is completed.

[0036] In some embodiments of the application, the continuous flow adsorption refers to preparing the polyiodide chain functionalized covalent organic framework material into a membrane, and making an aqueous solution containing iodine ions pass through the membrane for adsorption through a continuous flow system.

[0037] Specifically, the material is prepared into a membrane for a continuous flow iodine ion adsorption system; the preparation method of the membrane is to suspend the polyiodide chain functionalized covalent organic framework material powder in water to form a uniform suspension, filter the suspension onto a nylon membrane substrate through vacuum filtration to form a uniform self-supporting membrane, and obtain a composite membrane after drying; the flow rate of the continuous flow system is 0.5-5 mL / min.

[0038] In some embodiments of the application, the water body includes one of iodine-containing wastewater, spiked tap water, salt lake brine, and seawater.

[0039] In some embodiments of the application, after the adsorption of iodine ions in the water body is completed, the material is regenerated by a hydrogen peroxide solution, and then the material is sequentially cleaned with DMF, deionized water, and anhydrous ethanol, and is dried at 75°C for 8-24 hours to realize regeneration of the adsorbent.

[0040] The application has the following beneficial effects:

[0041] (1) The application adopts a biological biomimetic strategy, simulates the mechanism of iodine enrichment of seaweed, realizes the innovative adsorption strategy of “iodine adsorbing iodine”, and breaks through the limitations of traditional ion exchange materials in capacity and selectivity.

[0042] (2) The polyiodide chain functionalized covalent organic framework material prepared by the application has a super-high adsorption capacity for aqueous iodine ions, and the adsorption capacity is 198-486 mg / g, which is much higher than most reported iodine ion adsorbents.

[0043] (3) The material of the application has a fast adsorption kinetics, and can reach adsorption equilibrium within 60 minutes, meeting the efficiency requirements in actual applications.

[0044] (4) The material of the present invention has excellent selectivity for iodide ions, even in F - ,Cl - ,Br - ,NO3 - ,HCO3 - ,AC - ,SO4 2- ,CO3 2- ,SiO3 2- ,PO4 3- In the presence of coexisting ions such as iodine, it can still maintain high adsorption performance for iodide ions (in a multi-ion solution containing 100 mg / L of each of the above ions, the removal efficiency of iodide ions exceeds 90%).

[0045] (5) The material of the present invention exhibits excellent practical application performance in complex environments such as salt lake brine and seawater, with an iodine ion removal rate of over 65%, providing strong support for practical environmental applications.

[0046] (6) The material of the present invention can be conveniently prepared into a film for use in a continuous flow adsorption system, achieving continuous and efficient iodide ion removal, and has good engineering application prospects.

[0047] (7) The material of the present invention has good regeneration performance. After 5 cycles of use, it can still maintain more than 85% of the initial adsorption capacity, which reflects the economy and sustainability of the material.

[0048] (8) The preparation method of the present invention is simple, mild, and environmentally friendly, and can be completed using common organic reagents and aqueous solution systems, making it suitable for large-scale production and practical applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 iCOF-Cl - 、iCOF-I - Schematic diagram of the synthetic route.

[0050] (a): Synthesis of chloride-containing cationic covalent organic frameworks (iCOF-Cl) using different aromatic dialdehyde building blocks - ) synthesis route, showing the formation of four different iCOF-Cl by Schiff base condensation reaction of 1,2,3-triaminoguanidine hydrochloride with different dialdehyde monomers - (Nap-COF-Cl - 、Nap-OH-COF-Cl - BP-COF-Cl - and BP-OH-COF-Cl - ) process;

[0051] (b): Route of synthesis of iodine-containing cationic covalent organic frameworks (iCOF-I - ) with potassium iodide as template, demonstrating the strategy of adding potassium iodide as template in the synthesis reaction system to realize framework morphology control and simultaneously introduce iodine ions as counterions.

[0052] Figure 2 iCOF-I - The structure characterization results of the materials. Among them:

[0053] (a): X-ray powder diffraction (PXRD) pattern of Nap-COF-I - (b): X-ray powder diffraction (PXRD) pattern of Nap-OH-COF-I - (c): X-ray powder diffraction (PXRD) pattern of BP-COF-I - (d): X-ray powder diffraction (PXRD) pattern of BP-OH-COF-I - (e) is the Fourier transform infrared (FT-IR) spectrum of the four iCOF-I - materials, showing the characteristic absorption peaks of key functional groups in the materials.

[0054] Figure 3 X-ray powder diffraction (PXRD) pattern of iCOF-Cl - materials. Among them:

[0055] (a): X-ray powder diffraction (PXRD) pattern of Nap-COF-Cl - (b): X-ray powder diffraction (PXRD) pattern of Nap-OH-COF-Cl - (c): X-ray powder diffraction (PXRD) pattern of BP-COF-Cl - (d): X-ray powder diffraction (PXRD) pattern of BP-OH-COF-Cl - .

[0056] Figure 4 FT-IR spectrum of the four iCOF-Cl - materials. Among them:

[0057] (a): FT-IR spectrum of Nap-COF-Cl - (b): FT-IR spectrum of Nap-OH-COF-Cl - (c): FT-IR spectrum of BP-COF-Cl - (d): FT-IR spectrum of BP-OH-COF-Cl - .

[0058] Figure 5 Solid-state carbon nuclear magnetic resonance spectrum of the four iCOF-I - materials. Among them:

[0059] (a): Nap-COF-I - , (b): Nap-OH-COF-I - , (c): BP-COF-I - , (d): BP-OH-COF-I - .

[0060] Figure 6 are the N2adsorption-desorption isotherms of the four iCOF-I - materials. Among them:

[0061] (a): Nap-COF-I - , (b): Nap-OH-COF-I - , (c): BP-COF-I - , (d): BP-OH-COF-I - .

[0062] Figure 7 are the thermogravimetric curves of the four iCOF-Cl - and four iCOF-I - materials.

[0063] (a): Nap-COF-Cl - and Nap-COF-I - , (b): Nap-OH-COF-Cl - and Nap-OH-COF-I - , (c): BP-COF-Cl - and BP-COF-I - , (d): BP-OH-COF-Cl - and BP-OH-COF-I - .

[0064] Figure 8 are the PXRD patterns of Nap-OH-COF-I - and BP-OH-COF-I - before and after treatment in different reagents for 3 days, among which:

[0065] (a): Nap-OH-COF-I - PXRD patterns before and after treatment with 0.5 M HC1, 0.5 M NaOH, DMF, THF, ethanol and cyclohexane for 3 days.

[0066] (b): BP-OH-COF-I - PXRD patterns before and after treatment with 0.5 M HC1, 0.5 M NaOH, DMF, THF, ethanol and cyclohexane for 3 days.

[0067] Figure 9 Nap-OH-COF-I - and BP-OH-COF-I - FT-IR spectra before and after treatment in different reagents for 3 days, in which:

[0068] (a): Nap-OH-COF-I - FT-IR spectra before and after treatment in 0.5 M HC1, 0.5 M NaOH, DMF, THF, ethanol and cyclohexane for 3 days.

[0069] (b): BP-OH-COF-I - FT-IR spectra before and after treatment in 0.5 M HC1, 0.5 M NaOH, DMF, THF, ethanol and cyclohexane for 3 days.

[0070] Figure 10 Morphology and elemental composition of iCOF. In which:

[0071] (a): Nap-COF-Cl - SEM images of (b): Nap-OH-COF-Cl - SEM images of (c): BP-COF-Cl - SEM images of (d): BP-OH-COF-Cl - SEM images of (e): Nap-COF-I - SEM images of (f): Nap-OH-COF-I - SEM images of (g): BP-COF-I - SEM images of (h): BP-OH-COF-I - X-ray photoelectron spectroscopy (XPS) of (i): iCOF-Cl - X-ray photoelectron spectroscopy (XPS) of (j): iCOF-I - Transmission electron microscopy energy dispersive X-ray mapping (TEM-EDX) of (k): Nap-OH-COF-Cl - Transmission electron microscopy energy dispersive X-ray mapping (TEM-EDX) of (l): Nap-OH-COF-I -

[0072] Figure 11 Adsorption performance of iCOF for iodine ions in water. In which:

[0073] (a): Nap-COF-Cl - and Nap-OH-COF-Cl - ​pH dependent removal of iodide ions; (b) : iCOF-Cl - Adsorption kinetics of the material; (c) : iCOF-Cl - Adsorption isotherm of the material; (d) : Schematic of iCOF-Iodine adsorbent preparation and iodide ion capture; (e) : Adsorption kinetics of iCOF-Iodine material; (e) : Adsorption isotherm of iCOF-Iodine material; (g) : Elemental analysis and scanning electron microscopy energy dispersive mapping of Nap-OH-COF-Iodine after iodide ion adsorption.

[0074] Figure 12 iCOF-Cl - Zeta potential and particle size distribution of the material.

[0075] Figure 13 Selective adsorption of iodide ions in water by iCOFs. Wherein:

[0076] (a) : Performance comparison with other reported materials; (b) : Iodide ion removal efficiency of Nap-OH-COF-Iodine in the presence of competing ions; (c) : Iodide ion removal efficiency in real environmental samples; (d) : iCOF-Cl - Saturation adsorption capacity in high concentration chloride environment; (e) : Saturation adsorption capacity of iCOF-Iodine in high concentration chloride environment; (f) : Regenerated I2@Nap-OH-COF-I - Saturation adsorption capacity in high concentration chloride environment; (g) : Breakthrough curve of tri-iodide dynamic flow adsorption; (h) : UV-Vis absorption spectrum of Nap-OH-COF-Iodine after adsorbing tri-iodide; (i) : UV-Vis absorption spectrum of BP-OH-COF-Iodine after adsorbing tri-iodide.

[0077] Figure 14 I - Reusability of iCOFs after adsorption-desorption cycles.

[0078] Figure 15 Iodide ion removal efficiency of iCOF-Iodine in the presence of other interfering ions or real environmental samples.

[0079] Figure 16 Water contact angle of four iCOF-Iodine materials.

[0080] Figure 17 Adsorption mechanism of iodide ions. Wherein:

[0081] (a): Raman spectrum of Nap-OH-COF-Iodine; (b): Raman spectrum of BP-OH-COF-Iodine; (c): I 3d X-ray photoelectron spectrum of Nap-OH-COF-Iodine; (d): I 3d X-ray photoelectron spectrum of BP-OH-COF-Iodine; (e): Energy change diagram of converting I - to I2 / I3 - / I5 - ; (f): Energy change diagram of converting I - to I2 / I3 - / I5 - ; (g): Energy change diagram of converting I - to I2 / I3 - / I5 - ; (h): Energy change diagram of converting I - to I2 / I3 - / I5 - ; (i): N 1s X-ray photoelectron spectrum before iodine ion adsorption. (j): N 1s X-ray photoelectron spectrum after iodine ion adsorption. (k): O 1s X-ray photoelectron spectrum before iodine ion adsorption. (1): O 1s X-ray photoelectron spectrum after iodine ion adsorption.

[0082] Figure 18 is I 3d XPS spectrum of iCOF-Iodine after iodine ion adsorption.

[0083] Figure 19 are N 1s and O 1s XPS spectra of iCOF-Iodine before and after iodine ion adsorption. DETAILED DESCRIPTION

[0084] In order to make the objects, technical solutions and advantages of the embodiments of the present application clearer, the embodiments of the present application will be described in further detail. Obviously, the described embodiments are only a part but not all of the embodiments of the present application. Based upon the description of this specification, any ordinary skilled person in the art can obtain the other various embodiments without any creative work, and all the embodiments belong to the protection scope of the present application.

[0085] Unless otherwise specified, the raw materials and reagents used in the embodiments are purchased from regular commercial channels, or can be obtained by known methods. The definitions of scientific and technical terms follow the general specifications in the art. "About" means that the value floats within 10%, more preferably 5%, and most preferably 1% of the value. "Range" also includes all sub-ranges and their specific numerical values (whether specified or not).

[0086] The core mechanism of biological systems (such as seaweed) to efficiently enrich iodide ions is to realize efficient capture and concentration of iodide ions through specific redox reactions and formation of polyiodide chain structures. The adsorbent material of the present application can form a special polyiodide chain structure in the structure, which can break through the performance bottleneck of traditional adsorbents. Cationic covalent organic frameworks (iCOFs) provide an ideal platform for designing new iodine ion adsorbents due to their permanent pore structure, adjustable functional groups and intrinsic positive charge characteristics. Through functional modification, especially the introduction of hydrophilic functional groups such as hydroxyl groups, the interaction between the material and iodide ions in water can be further enhanced. However, how to effectively integrate the "iodine adsorbing iodine" mechanism in biological systems into synthetic materials to form stable polyiodide chain structures and be used for efficient adsorption of iodide ions in aqueous phase still faces many scientific challenges. In the redox process, the formation of polyiodide anions (IO n - ) is a key step, and these polyiodide species can form strong interactions with additional iodide ions through halogen bonds and charge transfer. Such polyiodide chain structures are difficult to exist stably in traditional inorganic materials, and carefully designed porous organic frameworks may provide an ideal microenvironment for this.

[0087] All adsorption experiments of the present application are repeated three times and the average value is taken, and the whole reaction process is avoided to exclude the interference of photodegradation.

[0088] Cationic covalent organic frameworks (iCOFs) are synthesized by two different methods: one is the traditional solvothermal method of chlorine-containing framework (iCOF-Cl - series), and the other is the innovative potassium iodide crystal template method of iodine-containing framework (iCOF-I - series), as shown in the accompanying Figure 1 .

[0089] Example 1

[0090] The synthesis method of iCOF-Cl - includes the following steps:

[0091] Synthesis of Nap-COF-Cl -To a mixture of 1,2,3-triaminoguanidine hydrochloride (28.2 mg, 0.2 mmol) and naphthalene-2,6-dicarboxaldehyde (55.3 mg, 0.3 mmol) in a solvent mixture consisting of 1,4-dioxane (3 mL) and mesitylene (1.5 mL), 6 M acetic acid (0.5 mL) was added as a catalyst. The reaction mixture was transferred to a polytetrafluoroethylene-lined stainless steel autoclave, which was sealed and heated at 120 °C for 72 h. Following a similar procedure, Nap-OH-COF-Cl - .

[0092] For BP-COF-Cl - To a mixture of 1,2,3-triaminoguanidine hydrochloride (28.2 mg, 0.2 mmol) and [1,1'-biphenyl]-4,4'-dicarboxaldehyde (63.1 mg, 0.3 mmol) in a mixture of o-dichlorobenzene (2.5 mL) and n-butanol (2.5 mL), 6 M acetic acid (0.5 mL) was added as a catalyst. The reaction mixture was transferred to a polytetrafluoroethylene-lined stainless steel autoclave, which was sealed and maintained at 120 °C for 72 h. Likewise, BP-OH-COF-Cl - was prepared by reacting 1,2,3-triaminoguanidine hydrochloride (28.2 mg, 0.2 mmol) with 3,3'-dihydroxy-[1,1'-biphenyl]-4,4'-dicarboxaldehyde (72.7 mg, 0.3 mmol) under the same reaction conditions.

[0093] After synthesis, all crude products were thoroughly purified to remove unreacted monomers and residual solvent molecules. The specific purification procedure was as follows: the solid product was collected by filtration and washed with 50 mL of DMF, 50 mL of THF, and 50 mL of dichloromethane, respectively, in a solvent filtration apparatus. The purified iCOF-Cl - The sample was immersed in 50 mL of a saturated ammonium bicarbonate solution at room temperature with stirring for 6 h, followed by the addition of 20 mL of isopropanol and stirring for 1 h to induce the recrystallization of ammonium bicarbonate in the COF pores. This method can effectively prevent the collapse of the framework due to capillary forces during solvent evaporation. The material was then dried at 100 °C overnight to obtain the activated iCOF-Cl - The product was stored in a sealed glass bottle for further characterization and application.

[0094] Example 2

[0095] iCOF-I - was synthesized following the procedure described above for iCOF-Cl

[0096] iCOF-I - Series were synthesized using a novel crystalline template method that uses potassium iodide as both a template and iodine source.

[0097] Synthesis of Nap-COF-I - When 1,2,3-triaminoguanidine hydrochloride (28.2 mg, 0.2 mmol) and naphthalene-2,6-dicarboxaldehyde (55.3 mg, 0.3 mmol) were mixed in a solvent mixture consisting of 1,4-dioxane (3 mL) and mesitylene (1.5 mL), followed by the addition of 6 M acetic acid (0.5 mL) as a catalyst and potassium iodide crystals (1 g) as a templating agent. The reaction mixture was transferred to a polytetrafluoroethylene-lined stainless steel autoclave, which was sealed and heated at 120 °C for 72 h. Following a similar procedure, Nap-OH-COF-I - .

[0098] For BP-COF-I - When 1,2,3-triaminoguanidine hydrochloride (28.2 mg, 0.2 mmol) and [1,1'-biphenyl]-4,4'-dicarboxaldehyde (63.1 mg, 0.3 mmol) were combined in a mixture of o-dichlorobenzene (2.5 mL) and n-butanol (2.5 mL), with 6 M acetic acid (0.5 mL) as a catalyst and potassium iodide crystals (1 g) as a templating agent. The reaction mixture was transferred to a polytetrafluoroethylene-lined stainless steel autoclave, which was sealed and maintained at 120 °C for 72 h. Likewise, BP-OH-COF-I - was prepared by reacting 1,2,3-triaminoguanidine hydrochloride (28.2 mg, 0.2 mmol) with 3,3'-dihydroxy-[1,1'-biphenyl]-4,4'-dicarboxaldehyde (72.7 mg, 0.3 mmol) under the same reaction conditions.

[0099] After synthesis, all crude products were thoroughly purified to remove unreacted monomers and residual solvent molecules. The specific purification steps were as follows: the solid product was collected by filtration and washed with 50 mL of DMF, 50 mL of deionized water, 50 mL of THF, and 50 mL of dichloromethane in a solvent filtration apparatus, respectively. Purified iCOF-I -The sample was immersed in 50 mL of saturated ammonium bicarbonate solution at room temperature for 6 hours, followed by the addition of 20 mL of isopropanol and stirring for 1 hour to induce recrystallization of ammonium bicarbonate in the COF pores. This method can effectively prevent the collapse of the framework due to capillary forces during the evaporation of the solvent. The material was then dried at 100 ° C overnight to obtain activated iCOF-I - The product was stored in a sealed glass bottle for further characterization and application.

[0100] iCOF-I - The reaction conditions of the framework are the same as those of iCOF-Cl in Example 1. - The counterparts were identical with one key change, namely the addition of potassium iodide crystals (1 g) to each reaction vessel. Figure 1 As shown in (b), this template strategy promotes the controlled assembly of COF networks through three stages: (1) the monomer is initially adsorbed on the surface of the potassium iodide crystal, (2) the ordered framework grows along the lattice structure, and (3) the potassium iodide template is subsequently dissolved, releasing the templated COF nanosheets. After the reaction is completed, the remaining bulk potassium iodide crystals are carefully removed with tweezers and then subjected to a standard washing process. An additional deionized water washing step is also performed to ensure the complete removal of residual potassium iodide. This crystal template method not only promotes the incorporation of iodide ions as counterions into the framework, but also significantly improves the structural order of the resulting material.

[0101] Since iCOF-I - The inherent iodine counterions in the framework prevent it from being used directly as an iodide ion adsorbent. - Due to the limitations of the material in iodide ion adsorption, the present invention uses 10% hydrogen peroxide solution to treat the freshly synthesized iCOF-I - The material oxidizes the inherent iodine ions in the framework to form polyiodine chains (I n - ), the obtained modified material (iCOF-Iodine) exhibited significantly enhanced iodide ion capture ability.

[0102] The synthesis method of iCOF-Iodine comprises the following steps:

[0103] Accurately weigh 500 mg of pre-synthesized iCOF-I in a clean, dry 100 mL beaker. - Then, 50 mL of freshly prepared 10% hydrogen peroxide solution was carefully added using a pipette. At the same time, a stirring bar was placed in the beaker and placed on a magnetic stirrer. The magnetic stirrer was turned on and set to a stirring speed of 300 rpm to ensure that the iCOF-I - The materials were fully dispersed in the solution and then reacted at room temperature for 12 hours to promote the iCOF-I- The oxidation reaction between iodide ions and hydrogen peroxide in the solution was observed, where the solution color gradually changed from colorless to brownish yellow, indicating the formation of polyiodide chains. After the reaction was completed, the solid product was collected using a vacuum filtration apparatus, and then the collected solid product was sequentially washed with 30 mL of DMF, 30 mL of deionized water, and 30 mL of anhydrous ethanol, respectively. Each time, the solid should be well dispersed to ensure complete washing. Next, the washed solid product was dried in a vacuum oven at 75 °C overnight to remove all residual solvents. After drying, the product iCOF-Iodine was stored in a dry, light-protected, sealed glass bottle to avoid exposure to air.

[0104] As shown in Figure 1 , a series of ion-covalent organic frameworks (iCOFs) with different structural features were successfully synthesized through Schiff base condensation reactions between guanidinium triaminate and various aromatic dialdehydes. Using naphthyl or biphenyl units, with or without hydroxyl functionalization, four different frameworks were prepared (labeled Nap-COF, Nap-OH-COF, BP-COF, and BP-OH-COF, respectively). Each framework was doped with either chloride (Cl - ) or iodide (I - ) ions as counterions, resulting in eight different iCOF materials. Powder X-ray diffraction (PXRD) analysis confirmed the successful formation of the crystalline frameworks. As shown in Figure 2 (a)-(d), Nap-COF-I - , Nap-OH-COF-I - , BP-COF-I - , and BP-OH-COF-I - exhibited strong diffraction patterns with strong peaks at approximately 4.18°, 4.46°, 3.56°, and 3.65° corresponding to the (100) reflection plane. Additional peaks at higher 2θ values further indicated the formation of ordered structures. The experimental PXRD patterns were highly matched with simulated patterns derived from the predicted AA stacking model, indicating that this stacking mode was dominant in the synthesized frameworks. The refined unit cell parameters and lower R p values (3.81%-4.30%) further verified the structural model. Similarly, iCOFs-Cl - showed similar diffraction patterns Figure 3 , confirming that counterion exchange did not significantly alter the crystalline framework structure. Fourier-transform infrared spectroscopy (FT-IR) provided strong evidence for the successful formation of imine bonds in these frameworks. As shown in Figure 2 (e) and Figure 4 , all iCOFs showed characteristic imine peaks at approximately 1610-1617 cm -1exhibiting characteristic C=N stretching vibrations, confirming the successful condensation reaction between the aldehyde and amine functional groups. The disappearance of the aldehyde C=0 stretching band (-1680 cm -1 ) and the significant attenuation of the primary amine N-H stretching signal (-3200-3300 cm -1 ) in the iCOF spectra compared to the respective monomers further confirmed the formation of the imine linkage. Solid-state 13 C NMR spectroscopy Figure 5 further verified the molecular structure of the synthesized frameworks. All spectra showed a characteristic signal at about 150-160 ppm, which can be attributed to the carbon atom in the newly formed C=N bond. The remaining resonance signals correspond well to the aromatic carbon environments of the naphthalene or biphenyl moieties. The spectral assignments were consistent with the proposed structural model, providing additional confirmation for the successful formation of the frameworks.

[0105] The pore characteristics of the iCOF materials were evaluated by nitrogen adsorption-desorption isotherms at 77 K Figure 6 ). The Brunauer-Emmett-Teller (BET) specific surface areas of Nap-COF-I - , Nap-OH-COF-I - , BP-COF-I - , and BP-OH-COF-I - were 127.3 m 2 / g, 108.5 m 2 / g, 142.4 m 2 / g, and 243.5 m 2 / g, respectively, with pore size distributions mainly centered at 1.71 nm, 1.69 nm, 1.92 nm, and 1.88 nm. Thermogravimetric analysis (TGA) demonstrated the excellent thermal stability of these iCOF materials Figure 7 , with all the framework structures remaining intact at least up to 247 °C. Notably, the type of counterion (CI - or I - ) had little effect on the thermal stability, indicating that the framework decomposition was mainly determined by the organic framework rather than the ionic component. The chemical stability of representative iCOFs (Nap-OH-COF-I - and BP-OH-COF-I - ) was evaluated by exposing the materials to various chemical environments, including acidic (0.5 M HC1), basic (0.5 M NaOH), and a variety of organic solvents (DMF, THF, ethanol, and cyclohexane), as shown in Figure 8 and Figure 9 . Notably, the PXRD patterns and FT-IR spectra of the treated samples remained essentially unchanged compared to the original materials, demonstrating their excellent chemical stability.

[0106] Scanning electron microscopy (SEM) observations revealed that the synthesized iCOFs exhibited a unique morphology ( Figure 10 (a)-(h)). Most frameworks formed a three-dimensional network with interconnected fibrous structures, creating a hierarchical pore structure. Notably, Nap-OH-COF exhibited a unique petal-like morphology consisting of interwoven nanosheets (20-50 nm thick) assembled into a multilayer structure ( Figure 10 (b) and (f)). This unique structure may originate from the enhanced π-π stacking between naphthalene rings and the hydrogen bonding network between hydroxyl groups, which enhance the interlayer interaction. X-ray photoelectron spectroscopy (XPS) analysis confirmed the elemental composition of all frameworks, showing the characteristic peaks of the framework components (C 1s, N 1s, O 1s), as well as the iCOF-Cl - Cl 2p (~198.5eV) or iCOF-I in the material - I 3d in the material (~619.0eV, ~630.0eV) ( Figure 10 The absence of chloride signals in the iCOF-I-spectrum confirms the completeness of the counterion exchange using the potassium iodide template method. Transmission electron microscopy energy dispersive X-ray spectroscopy (TEM-EDX) mapping ( Figure 10 (k) and (l) show that all elements are evenly distributed in the framework, confirming that guanidine hydrochloride is successfully integrated into the framework structure rather than being confined to the surface.

[0107] Example 3

[0108] The adsorption experiment of iodide ions in aqueous phase includes the following steps:

[0109] The adsorption behavior of iodide ions on the synthesized iCOFs was systematically studied by batch equilibrium experiments. A potassium iodide stock solution (500 mg / L) was prepared using distilled water and subsequently diluted to obtain a series of iodide ion solutions with concentrations ranging from 2 to 250 mg / L. For pH-dependent adsorption studies, 10 mg of iCOF adsorbent was added to 20 mL of iodide ion solution (100 mg / L), and the pH value was adjusted between 2 and 11 using 0.5 M hydrochloric acid or sodium hydroxide solution. The suspension was stirred continuously at room temperature for 60 minutes to reach adsorption equilibrium. After centrifugation, the concentration of residual iodide ions in the supernatant was determined, and the removal efficiency was calculated according to the following formula:

[0110]

[0111] where c0 and c e (mg / L) represent the initial concentration and equilibrium concentration of iodide ions, respectively.

[0112] Adsorption kinetics experiments were performed by dispersing 25 mg of iCOF in 50 mL of iodide solution (250 mg / L, pH = 7) under continuous stirring at room temperature. At predetermined time intervals, aliquots of the suspension were withdrawn, and the residual iodide concentration was analyzed after centrifugation. For adsorption isotherm studies, a similar experimental procedure was adopted, but the initial iodide concentration was varied from 20 to 250 mg / L, while other experimental parameters were kept constant. The equilibrium adsorption capacity (q e , mg / g) was calculated using the following equation:

[0113]

[0114] where V (L) is the solution volume and m (g) is the mass of iCOF adsorbent. All batch adsorption experiments were performed in triplicate to ensure reproducibility, and the average values are reported. Iodide concentration was mainly determined by UV-Vis absorption spectroscopy by monitoring the characteristic absorption peak at ~226 nm. However, for complex matrices containing multiple ionic species, inductively coupled plasma optical emission spectrometry / mass spectrometry (ICP-OES / MS) techniques were employed for more accurate quantitative analysis.

[0115] The present invention investigated the removal of aqueous iodide by two cationic iCOF materials: the use of iCOF-Cl - materials by conventional anion exchange method and the use of modified iCOF-I - materials by a biomimetic strategy. pH-dependent studies Figure 11 (a) showed that iCOF-Cl - materials performed best in the pH = 2-7 range, with the hydroxyl-functionalized variants maintaining high removal efficiency over a wider pH range, which indicates that iodide stability is enhanced by supplementary hydrogen bonding. This behavior is consistent with zeta potential measurements Figure 12 ), which show a transition from positive to negative values at approximately pH = 8-9. Adsorption kinetics Figure 11 (b) revealed a two-stage process: a rapid adsorption within 15 min, followed by an equilibrium within 60 min. Nap-OH-COF-Cl - exhibited the highest adsorption capacity (281.9 mg / g), followed by BP-OH-COF-Cl - (223.6 mg / g), BP-COF-Cl - (151.8 mg / g), and Nap-COF-Cl - (124.5 mg / g). Kinetic models were best fitted to the pseudo-second-order kinetic model (R 2 > 0.99, Table 1), indicating that chemical adsorption is the rate-limiting step. Adsorption isotherms Figure 11(c)) is consistent with the Langmuir model (R 2 >0.999, Table 2), indicating that iodide ions undergo monolayer adsorption on the uniform surface.

[0116] Although iCOF-Cl - The material exhibits excellent adsorption performance. The iCOF-I synthesized by the present invention - The inherent iodine counterions in the frameworks hinder their direct use as iodide ion adsorbents. To overcome the iodine-containing iCOF-I - In order to overcome the limitations of the materials in iodide ion adsorption, the present invention developed a biomimetic method. Figure 11 As shown in (d), iCOF-I - The material was treated with 10% hydrogen peroxide to oxidize the inherent iodine ions in the framework to form polyiodine chains (I n - ). These modified materials (iCOF-Iodine) showed significantly enhanced iodide ion capture ability. iCOF-Iodine materials showed accelerated adsorption rate ( Figure 11 In (e), the equilibrium adsorption capacity almost doubled: Nap-OH-COF-Iodine (486.1 mg / g), BP-OH-COF-Iodine (385.0 mg / g), Nap-COF-Iodine (207.2 mg / g) and BP-COF-Iodine (198.4 mg / g). The kinetic model confirmed the pseudo-second-order kinetic model (R 2 >0.99, Table 3), the higher intra-particle diffusion constant indicates that the mass transfer efficiency has been improved. Adsorption isotherm ( Figure 11 (f), Table 4) shows good agreement with the Langmuir model (R 2 >0.998), with maximum adsorption capacities of 500.0 mg / g for Nap-OH-COF-Iodine, 400.0 mg / g for BP-OH-COF-Iodine, 243.9 mg / g for Nap-COF-Iodine, and 212.8 mg / g for BP-COF-Iodine. This exceptional performance stems from a charge transfer-driven "snowball" effect, in which the polyiodine chains promote the continued enrichment of additional iodide ions by forming extended polyiodine species. Elemental analysis and mapping ( Figure 11 Figure (g) demonstrates the increased iodine content and uniform distribution within the framework. The superior performance of hydroxyl-functionalized materials stems from synergistic factors: the creation of nucleation sites by the multiple iodide chains, the strong electrostatic interactions generated by the cationic backbone, the additional hydrogen bonding provided by the hydroxyl groups, and the optimized pore structure. This biomimetic "iodine-attracting-iodine" approach transforms structural limitations into functional advantages for advanced iodine-capturing materials.

[0117] Table 1 Adsorption kinetics fitting parameters for iodide ions on iCOF-Cl -

[0118]

[0119]

[0120] Table 2 Adsorption isotherm fitting parameters for iodide ions on iCOF-Cl -

[0121]

[0122] Table 3 Adsorption kinetics fitting parameters for iodide ions on iCOF-Iodine

[0123]

[0124] Table 4 Adsorption isotherm fitting parameters for iodide ions on iCOF-Iodine

[0125]

[0126] Example 4

[0127] The selective adsorption of iodide ions in aqueous phase was studied, including the following steps:

[0128] To evaluate the adsorption selectivity of iCOF for iodide ions, batch adsorption experiments were performed in the presence of competing anions, using solutions containing F - , Cl - , Br - , NO3 - , HCO3 - , AC - (acetate), SO4 2- , CO3 2- , SiO3 2- , PO4 3- ​​polyanionic solutions. In addition, the effect of chloride ions on iodide ion adsorption was also specifically investigated using binary solutions containing both iodide ions (250 mg / L) and chloride ions (1000 mg / L) at neutral pH. To evaluate the practical applicability of the synthesized iCOF for the removal of iodide ions from complex environmental matrices, adsorption experiments were performed using real environmental samples, including a salt lake brine from the Chaxian Salt Lake and seawater from the Bohai Sea. Prior to the adsorption experiments, these environmental samples were filtered through 0.22 micron nylon membranes to remove insoluble impurities. Typically, 25 mg of iCOF was dispersed in 50 mL of the filtered environmental sample and stirred for 60 minutes at room temperature. The suspension was subsequently centrifuged and the supernatant was analyzed using ICP-OES / MS to determine the residual concentrations of iodide ions and other competing ions, thereby evaluating the selective adsorption performance of iCOF under real conditions.

[0129] With record capacity, exceptional reusability, and fast kinetics Figure 13 in (a), Table 5, and Figure 14 ), Nap-OH-COF-Iodine becomes a promising candidate material for nuclear waste treatment and environmental remediation applications. The iCOF-Iodine after adsorbing iodide ions was immersed in a 10% hydrogen peroxide solution for 24 hours for regeneration, thereby fully oxidizing the adsorbed iodide ions into elemental iodine and iodine oxides. After the solid was separated by filtration, the material was sequentially washed with DMF, deionized water, and anhydrous ethanol to remove the surface residual iodine species. The washed iCOF-Iodine material was then dried at 75°C overnight for reuse in the next adsorption cycle. After five consecutive adsorption-desorption cycles, the adsorption capacity of Nap-OH-COF-Iodine for iodide ions remained 94.8% of the original adsorption capacity. The adsorption selectivity of the material was tested under the coexistence of various interfering ions with iodide ions to evaluate its practical application value. When common competitive anions (F - , Cl - , Br - , NO3 - , HCO3 - , AC - , SO4 2- , CO3 2- , SiO3 2- , PO4 3- ) were tested at equal concentrations with iodide ions, Nap-OH-COF-Iodine maintained consistently high removal efficiency (>90%) Figure 13 in (b)) in all cases. Similar results were also observed for other iCOF-Iodine materials Figure 15This exceptional selectivity stems from a polyiodide-mediated capture mechanism, in which the strong affinity between the growing polyiodide chain and the incoming iodide ion forms an energetically more favorable species that can outcompete other anions. Figure 13 (c) Figure 15 All iCOF-Iodine materials maintained satisfactory removal efficiencies (65.8-95.2%) in a variety of samples, including Qarhan Salt Lake brine, iodide-spiked tap water, and authentic Bohai Sea water. The poorer efficiency in the salt lake samples reflects the effects of the extremely high concentrations of chloride and sulfate typical of salt lake environments.

[0130] Given that chloride is the most abundant and potentially interfering anion in natural waters, we conducted a detailed comparative study of the chloride resistance of the materials. The comparative study of chloride resistance showed that when the chloride concentration was four times that of the iodide concentration (C I - =250 mg / L), iCOF-Cl - The material showed a significant capacity decrease (42.5-58.1%) ( Figure 13 In contrast, the iCOF-Iodine materials exhibit significantly enhanced resistance, with minimal capacity degradation: 7.5% for Nap-OH-COF-Iodine, 8.3% for BP-OH-COF-Iodine, 15.1% for BP-COF-Iodine, and 14.6% for Nap-COF-Iodine (Fig. Figure 13 (e)). This improvement highlights the advantage of the polyiodide-mediated capture mechanism, which relies on specific iodine-iodine interactions rather than just electrostatic attraction. In addition, Nap-OH-COF-I, which had previously captured I2 vapor and then desorbed by ethanol, - It also showed a significant iodide ion adsorption capacity (304.2 mg / g), reaching about 85% of the saturated adsorption capacity observed in chloride-free solution without H2O2 treatment ( Figure 13 This reveals that residual iodine species can also promote the “iodine-by-iodine” mechanism, highlighting the potential of these materials for continuous gas- and aqueous-phase iodine capture.

[0131] Table 5 Comparison of the materials of this application with reported adsorbents

[0132]

[0133] (1) Lefevre, G.; Walcarius, A.; Ehrhardt, J.-J.; Bessiere, J. Sorption of iodide on cuprite (Cu20). Langmuir 2000, 16 (10), 4519-4527.

[0134] (2) Mao, P.; Qi, B.; Liu, Y.; Zhao, L.; Jiao, Y.; Zhang, Y.; Jiang, Z.; Li, Q.; Wang, J.; Chen, S. AgII doped MIL-101 and its adsorption of iodine with high speed in solution. Journal of Solid State Chemistry 2016, 237, 274-283.

[0135] (3) (3) Misaelides, P.; Petrus, R.; Zamboulis, D. Preparation and application of organo-modified zeolitic material in the removal of chromates and iodides. Journal of Hazardous Materials 2006, 137 (3), 1410-1416.

[0136] (4) Choung, S.; Um, W.; Kim, M.; Kim, M.-G. Uptake mechanism for iodine species to black carbon. Environmental science & technology 2013, 47 (18), 10349-10355.

[0137] (5) Mao, P.; Liu, Y.; Jiao, Y.; Chen, S.; Yang, Y. Enhanced uptake of iodide on Ag@Cu20 nanoparticles. Chemosphere 2016, 164, 396-403.

[0138] (6) Hoskins, J. S.; Karanfil, T.; Serkiz, S. M. Removal and sequestration of iodide using silver-impregnated activated carbon. Environmental science & technology 2002, 36 (4), 784-789.

[0139] (7) Zhang, X.; Gu, P.; Li, X.; Zhang, G. Efficient adsorption of radioactive iodide ion from simulated wastewater by nano Cu2O / Cu modified activated carbon. Chemical Engineering Journal 2017, 322, 129-139.

[0140] (8) Lefevre, G.; Alnot, M.; Ehrhardt, J.; Bessiere, J. Uptake of iodide by a mixture of metallic copper and cupric compounds. Environmental science & technology 1999, 33 (10), 1732-1737.

[0141] (9) Choung, S.; Kim, M.; Yang, J.-S.; Kim, M.-G.; Um, W. Effects of radiation and temperature on iodide sorption by surfactant-modified bentonite. Environmental Science & Technology 2014, 48 (16), 9684-9691.

[0142] (10) Asmussen, R. M.; J.; Qafoku, N. P.; Kruger, A. A. Silver-functionalized silica aerogels and their application in the removal of iodine from aqueous environments. Journal of Hazardous Materials 2019, 379, 119364.

[0143] (11) Zhang, H.; Gao, X.; Guo, T.; Li, Q.; Liu, H.; Ye, X.; Guo, M.; Wu, Z. Adsorption of iodide ions on a calcium alginate-silver chloride composite adsorbent. Colloids and Surfaces A: Physicochemical and Engineering Aspects 2011, 386 (1-3), 166-171.

[0144] (12) Ye, Z.; Chen, L.; Liu, C.; Ning, S.; Wang, X.; Wei, Y. The rapid removal of iodide from aqueous solutions using a silica-based ion-exchanger resin. Reactive and Functional Polymers 2019, 135, 52-57.

[0145] (13) Liu, L.; Liu, W.; Zhao, X.; Chen, D.; Cai, R.; Yang, W.; Komarneni, S.; Yang, D. Selective capture of iodide from solutions by microrosette-like δ-Bi2O3. ACS Applied Materials & Interfaces 2014, 6 (18), 16082-16090.

[0146] (14) Liu, S.; Wang, N.; Zhang, Y.; Li, Y.; Han, Z.; Na, P. Efficient removal of radioactive iodide ions from water by three-dimensional Ag2O-Ag / TiO2 composites under visible light irradiation. Journal of hazardous materials 2015, 284, 171-181.

[0147] (15) Chen, J.; Gao, Q.; Zhang, X.; Liu, Y.; Wang, P.; Jiao, Y.; Yang, Y. Nanometer mixed-valence silver oxide enhancing adsorption of ZIF-8 for removal of iodide in solution. Science of the Total Environment 2019, 646, 634-644.

[0148] (16) Zhao, X.; Han, X.; Li, Z.; Huang, H.; Liu, D.; Zhong, C. Enhanced removal of iodide from water induced by a metal-incorporated porous metal-organic framework. Applied Surface Science 2015, 351, 760-764.

[0149] (17) Li, J.; Wang, M.; Liu, G.; Zhang, L.; He, Y.; Xing, X.; Qian, Z.; Zheng, J.; Xu, C. Enhanced iodide removal from water by nano-silver modified anion exchanger. Industrial & Engineering Chemistry Research 2018, 57(51), 17401-17408.

[0150] (18) Liu, S.; Kang, S.; Wang, H.; Wang, G.; Zhao, H.; Cai, W. Nanosheets-built flowerlike micro / nanostructured Bi2O2.33 and its highly efficient iodine removal performances. Chemical Engineering Journal 2016, 289, 219-230.

[0151] (19) Chen, Y.-Y.; Yu, S.-H.; Yao, Q.-Z.; Fu, S.-Q.; Zhou, G.-T. One-step synthesis of Ag2O@Mg(OH)2 nanocomposite as an efficient scavenger for iodine and uranium. Journal of Colloid and Interface Science 2018, 510, 280-291.

[0152] (20) Bo, A.; Sarina, S.; Zheng, Z.; Yang, D.; Liu, H.; Zhu, H. Removal of radioactive iodine from water using Ag2O grafted titanate nanolamina as efficient adsorbent. Journal of Hazardous Materials 2013, 246, 199-205. Example 5

[0153] Adsorption experiments of triiodide ions in aqueous phase, including the following steps:

[0154] To evaluate the adsorption efficiency of iCOF under dynamic breakthrough conditions, a series of adsorption experiments using triiodide ions (I3 -Experimental. First, a stock solution of triiodide ions (1.5 mmol) was prepared by dissolving 225 mg of sodium iodide (1.5 mmol) and 381 mg of iodine (1.5 mmol) in 1000 mL of deionized water. The successful formation of triiodide ions was confirmed by UV-Vis absorption spectroscopy, observing characteristic absorption bands at 287 nm and 351 nm, which are consistent with the spectral features of triiodide ions in aqueous solution. For the dynamic filtration experiments, iCOF membranes were prepared using a vacuum-assisted in situ deposition method. Specifically, 100 mg of synthesized iCOF powder was uniformly dispersed in 50 mL of deionized water under mild sonication, forming a uniform suspension. Then, the suspension was filtered onto a 50 mm diameter nylon membrane substrate by vacuum filtration, forming a uniform self-supporting iCOF membrane. After formation, the membrane was thoroughly rinsed with deionized water to remove any loosely bound particles, followed by air-drying at room temperature for 12 hours. The prepared iCOF membrane was carefully fixed between the middle layers of a stainless-steel filtration setup to ensure that the entire solution could pass through the membrane during the filtration process. The experimental setup was constructed by connecting the outlet of a peristaltic pump to the inlet of the filter housing using appropriate tubing, while the inlet tube of the pump was immersed in the 1.5 mmol triiodide ion stock solution. The dynamic adsorption process was initiated by activating the peristaltic pump at a controlled flow rate of 5 mL / min. To monitor the breakthrough behavior, effluent samples were collected every five minutes and immediately analyzed using UV-Vis absorption spectroscopy. The absorbance values at 286 nm were measured to determine the residual triiodide ion concentration in the filtered solution, which was used to calculate the removal efficiency as a function of time and treated solution volume. This experimental configuration allowed the performance of iCOF membranes to be evaluated under conditions closer to actual applications, where continuous flow and rapid adsorption kinetics are crucial for efficient removal of pollutants. The dynamic breakthrough experiment provided information on the adsorption capacity, selectivity, and stability of iCOF membranes under flow conditions.

[0155] For continuous flow applications, the hydroxyl-functionalized materials exhibit enhanced hydrophilicity Figure 16 ), facilitating water permeation and contaminant contact. The present invention evaluated the dynamic capture ability of these materials for triiodide ions (I3 - ), which are often formed in environmental water bodies in the presence of iodide and iodine. The breakthrough curves Figure 13 in (g) demonstrate superior triiodide ion retention capacity, with the BP-OH-COF-Iodine membrane exhibiting breakthrough after approximately 550 mL, and the Nap-OH-COF-Iodine membrane exhibiting breakthrough after approximately 800 mL. The UV-Vis absorption spectra Figure 13 in (h) and Figure 13(i)) confirmed that the concentration of triiodide ions gradually increased with increasing solution volume (peaks at 287 nm and 351 nm). These results indicate that the materials of the present invention are not only suitable for batch adsorption, but also for continuous flow applications in water treatment processes. This combination of high capacity, fast kinetics, excellent selectivity, and robust performance in complex matrices makes iodine-based iCOF materials one of the most promising candidates for practical iodide ion remediation. Its excellent selectivity stems from specific affinity sites created by polyiodine chains, which preferentially bind to iodide ions through halogen bonds and charge transfer interactions, forming a self-amplifying capture system similar to the biological iodine concentration mechanism in seaweed. Hydroxyl-functionalized variants further enhance selectivity by providing additional hydrogen bonding interactions, which stabilize the growing polyiodine species.

[0156] In order to clarify the microscopic interaction between iCOF-Iodine, which has excellent iodide ion capture performance, and iodide ions, the present invention conducted spectroscopic studies combined with theoretical calculations. The Raman spectra of Nap-OH-COF-Iodine and BP-OH-COF-Iodine ( Figure 17 (a) and Figure 17 (b) shows 104-135cm -1 (belongs to I3 - stretching vibration) and 151-175cm -1 (attributable to I n - The characteristic peaks of stretching vibration, n≥3) confirm the existence of multiple iodides in the framework channel. XPS analysis of the I 3d region ( Figure 17 (c) Figure 17 (d) and Figure 18 ) confirmed these findings. These spectra can be deconvoluted into three different chemical environments: the peak at about 619 eV (I5 - ), the peak at 630eV (I3 - ), and 617.27-618.08eV(I 3d 5 / 2 ) and 628.79-629.44eV(I 3d 3 / 2 ), indicating the presence of extended polyiodides. The hydroxyl-functionalized framework exhibited a higher proportion of extended polyiodides, which is consistent with its superior adsorption performance.

[0157] Density functional theory (DFT) calculations ( Figure 17 (e)-(h)) reveal the thermodynamically favorable pathway for iodide ion capture, first through I -Oxidation to I2, which then combines with additional iodide ions to form extended polyiodine chains. The hydroxyl-functionalized framework exhibits more favorable energetics in terms of the oxidation and chain formation steps. For Nap-OH-COF ( Figure 17 (f)), I - The energy barrier for conversion to I2 (-0.291 eV) is significantly lower than that of Nap-COF (0.105 eV), and the subsequent formation of I3 - and I5 - It is also more energetically favorable. BP-OH-COF( Figure 17 (h)) and BP-COF( Figure 17 A similar trend was observed in (g). XPS analysis of the N1s and O1s regions ( Figure 19 (i)-(l)) The electronic interactions between the framework components and the adsorbed polyiodide species were investigated. The N 1s spectra showed a significant shift in the binding energy of the C=N component after iodide adsorption (Nap-OH-COF from 399.87 eV to 399.23 eV), and a new peak at approximately 398.15 eV, which can be attributed to the charge transfer interaction, appeared. Similar shifts were observed for all materials ( ​ ), the hydroxyl functionalized variant showed a more obvious change. The O 1s spectrum also showed a binding energy shift after iodide ion adsorption (Nap-OH-COF-Iodine from 532.0eV to 531.6eV), indicating that the hydroxyl group participates in stabilizing the polyiodide chain. Based on these studies, the present invention provides a multi-step capture mechanism: (1) iodide ion (I - ) is oxidized to iodine molecules (I2) under the action of residual iodine species in the framework, and this process is promoted by the cationic environment; (2) the formed iodine molecules combine with additional iodide ions to generate triiodide ions (I3 - ); (3) These further interact to form extended iodine chains (I5 - 、I7 - Hydroxyl groups enhance this process by providing hydrogen bonding sites, increasing the hydrophilicity of the framework, and promoting charge transfer interactions with polyiodinated species. This "iodine-attracting iodine" mechanism fundamentally differs from traditional ion exchange in that it achieves higher capture capacity by extending the polyiodinated chains, imparting inherent selectivity for iodide ions through specific iodine-iodine interactions, and gradually increasing capture efficiency through thermodynamically favorable iodine species conversion.

[0158] It should be understood that although specific embodiments of the present invention have been shown and described in detail above, these embodiments are merely illustrative and should not be construed as limiting the scope of protection of the present invention. Persons skilled in the art may make various adjustments, optimizations, equivalent substitutions, or improvements to the above embodiments without departing from the spirit and scope of the present invention.

Claims

1. A covalent organic framework material functionalized with iodine chains, characterized in that: The material is formed by treating a cationic covalent organic framework (iCOF) with hydrogen peroxide. The cationic covalent organic framework contains an iodine chain structure in its pores. The iodine chain structure includes I3 - 、I5 - and polyiodide anions with higher polymerization degree; The cationic covalent organic framework is synthesized by a Schiff base condensation reaction of 1,2,3-triaminoguanidine hydrochloride and an aromatic dialdehyde; the aromatic dialdehyde is selected from at least one of naphthalene-2,6-dicarboxaldehyde, 2,6-dihydroxynaphthalene-1,5-dicarboxaldehyde, 4,4-biphenyldicarboxaldehyde, and 3,3'-dihydroxy-[1,1'-biphenyl]-4,4'-dicarboxaldehyde.

2. The iodine chain functionalized covalent organic framework material according to claim 1, characterized in that: The aromatic dialdehyde is selected from at least one of 2,6-dihydroxynaphthalene-1,5-dicarbaldehyde and 3,3'-dihydroxy-[1,1'-biphenyl]-4,4'-dicarbaldehyde.

3. A method for preparing a covalent organic framework material functionalized with an iodine chain, characterized in that: The following steps are involved: S1: 1,2,3-triaminoguanidine hydrochloride and an aromatic dialdehyde are mixed in a molar ratio of 1:(1.5-3), dissolved in a mixed solvent, glacial acetic acid solution is added as a catalyst, and sufficient potassium iodide or sodium iodide (≥0.18 g / mL) is added as a template reagent; the aromatic dialdehyde is selected from at least one of naphthalene-2,6-dicarboxaldehyde, 2,6-dihydroxynaphthalene-1,5-dicarboxaldehyde, 4,4-biphenyldicarboxaldehyde, and 3,3'-dihydroxy-[1,1'-biphenyl]-4,4'-dicarboxaldehyde; S2: reacting the mixed solution from step S1 in a sealed reactor at 80-120° C. for 24-72 hours; S3: The reaction product was collected by filtration, washed, and then immersed in a saturated ammonium bicarbonate solution at room temperature and stirred for 4-8 hours. Isopropanol was then added to the saturated ammonium bicarbonate solution and stirred for 0.5-2 hours. The solid product was separated by filtration and then dried at 75-100°C for 10-24 hours to obtain iCOF-I. - ; S4: iCOF-I - Disperse in an aqueous solution containing 5%-30% hydrogen peroxide and stir at room temperature for 6-12 hours; S5: The treated product is filtered, washed with DMF, then washed with deionized water until neutral, then washed with anhydrous ethanol, and finally dried at 75-100° C. for 10-24 hours to obtain a covalent organic framework material functionalized with an iodine chain; Preferably, the aromatic dialdehyde is selected from at least one of 2,6-dihydroxynaphthalene-1,5-dicarboxaldehyde and 3,3'-dihydroxy-[1,1'-biphenyl]-4,4'-dicarboxaldehyde; more preferably, the aromatic dialdehyde is selected from 2,6-dihydroxynaphthalene-1,5-dicarboxaldehyde.

4. The method for preparing a covalent organic framework material functionalized with an iodine chain according to claim 3, characterized in that: The mixed solvent in step S1 is a mixture of 1,4-dioxane and mesitylene, and more preferably, the volume ratio of the two is (1-2):1, or the mixed solvent is a mixture of o-dichlorobenzene and n-butanol, and more preferably, the volume ratio of the two is (1-2):

1. Preferably, when the aromatic dialdehyde is naphthalene-2,6-dicarboxaldehyde (Nap) or 2,6-dihydroxynaphthalene-1,5-dicarboxaldehyde (Nap-OH), the mixed solvent is a mixture of 1,4-dioxane and mesitylene in a volume ratio of (1-2):1; when the aromatic dialdehyde is 4,4-biphenyldicarboxaldehyde (BP) or 3,3'-dihydroxy-[1,1'-biphenyl]-4,4'-dicarboxaldehyde (BP-OH), the mixed solvent is a mixture of o-dichlorobenzene and n-butanol in a volume ratio of (1-2):

1. Preferably, the concentration of the glacial acetic acid solution is 6-9 M, and the volume ratio of the glacial acetic acid solution to the mixed solvent is 1:(3-10).

5. The method for preparing a covalent organic framework material functionalized with an iodine chain according to claim 4, characterized in that: When the aromatic dialdehyde is naphthalene-2,6-dicarboxaldehyde or 2,6-dihydroxynaphthalene-1,5-dicarboxaldehyde, the mixed solvent is a mixture of 1,4-dioxane and mesitylene, the concentration of the glacial acetic acid solution is 6M, and the volume ratio of 1,4-dioxane, mesitylene, and 6M glacial acetic acid solution is 6:3:1; When the aromatic dialdehyde is 4,4-biphenyldicarboxaldehyde or 3,3'-dihydroxy-[1,1'-biphenyl]-4,4'-dicarboxaldehyde, the mixed solvent is a mixture of o-dichlorobenzene and n-butanol, the concentration of the glacial acetic acid solution is 6M, and the volume ratio of o-dichlorobenzene, n-butanol, and 6M glacial acetic acid solution is 5:5:

1.

6. The method for preparing a covalent organic framework material functionalized with an iodine chain according to claim 3, characterized in that: In step S3, the washing refers to washing the reaction product with N,N-dimethylformamide, deionized water, tetrahydrofuran, and dichloromethane in sequence.

7. Application of a covalent organic framework material functionalized with an iodine chain for adsorbing (removing) iodide ions in water, characterized in that: The iodine chain functionalized covalent organic framework material is the iodine chain functionalized covalent organic framework material according to claim 1 or 2, or the iodine chain functionalized covalent organic framework material prepared by the method according to any one of claims 3 to 6.

8. The use according to claim 7, characterized in that The adsorption process adopts batch adsorption or continuous flow adsorption; Optionally, the batch adsorption refers to directly adding the above-mentioned iodine chain functionalized covalent organic framework material into an aqueous solution containing iodide ions, stirring and adsorbing at room temperature, and separating after the adsorption is completed; Optionally, the continuous flow adsorption refers to preparing the above-mentioned covalent organic framework material functionalized with polyiodine chains into a membrane, and allowing an aqueous solution containing iodine ions to pass through the membrane for adsorption through a continuous flow system.

9. The use according to claim 7, characterized in that The polyiodine chain functionalized covalent organic framework material is prepared into a membrane for a continuous flow iodide ion adsorption system; the membrane preparation method comprises suspending the polyiodine chain functionalized covalent organic framework material powder in water to form a uniform suspension, filtering the suspension onto a nylon membrane substrate by vacuum filtration to form a uniform self-supporting membrane, and obtaining a composite membrane after drying; the flow rate of the continuous flow system is 0.5-5 mL / min.

10. The use according to claim 7, characterized in that The water body includes one of iodine-containing wastewater, spiked tap water, salt lake brine, and seawater; And / or, after the iodine ions in the water are adsorbed, the material is regenerated by using a hydrogen peroxide solution, and then the material is washed with DMF, deionized water and anhydrous ethanol in sequence, and dried at 75° C. for 8-24 hours to achieve regeneration of the adsorbent.

Citation Information

Patent Citations

  • Two-dimensional covalent organic framework material with cationic skeleton, preparation method and application of two-dimensional covalent organic framework material and lithium metal battery electrode

    CN114262447A

  • Quercetin / covalent organic framework composite photocatalytic material as well as preparation method and application thereof

    CN118894974A

  • Method for removing and adsorbing iodide ion

    JP2012251912A